Prepovedane droge v slovenskih množičnih medijih - Drev, Andreja (Zdravstveno varstvo, 2006)
Aim: The purpose of the article was to establish the frequency of Slovene media reports on illicit drugs, as well as to identify the main initiators of media coverage of illicit drugs and to determine the influence of health institutions on the information provided. Method: During the period studied, we collected 360 articles on illicit drugs published in twelve selected Slovene mass media. Basic techniques of descriptive statistical analysis and statistical significance tests were used. The articles were analysed using theSPSS statistical package. Results: The publication of as many as 79.4 % of articles about illicit drug use was urged by non-media individuals and institutions, most frequently by non-governmental organizations (19.4 %) and health care institutions (17.5 %). Drug prevention was the subject area addresed by most articles (16.4 %); most contributions encouraged by health care organizations fell into the category "teenagers and drugs". Articles on illicit drugs were most frequently written by corresponding journalist and reporters (27.8 %) and appeared in regional news (23.6 %) and crime pages (19.2 %). As for the journalistic genre, 50 % of articles about illicit drugs were reports. Conclusions: Mass media do not see illicit drug problem as a high-priority health issue, and tend to criminalize illicit drugs and drug users. Articles on illicit drugs place insufficient emphasis on effects of drug-free lifestyles and on other aspects relevant to drug use prevention.
Keywords: analiza; droge; Health Education; journalism; Mass Media; Množična občila; množični mediji; Nedovoljene snovi; novinarstvo; prepovedane droge; prispevki; Street Drugs; Substance Abuse; Zdravstvena vzgoja